Pemanfaatan Obat Tradisional Dengan Pertimbangan Manfaat Dan Keamanannya - Kumala Sari, Lusia Oktora Ruma (Majalah Ilmu Kefarmasian, 2006)
Herbal medicines in general are safer than modern drug. This matter is caused by the less side effect of herbal medicines than modern drug. Side effects of herbal medicines can be reduced with the used of right materials, accurat dose, accurat usage time, accurat way of usage, accurat analyze information, and without abusing of herbal medicines itself. Accuracy of materials determine the effect of herbal medicines. Dose measuring in set of gram can lessen possibility the happening of effect which do not be expected. Information which is not supported by adequate basic knowledges and enough study can make traditional drug return to endangering.